An ethnobotanical study of wild plant resources used among locals of high mountainous regions of Swat Valley, Pakistan - Ali, Shujat; Shah, Sayed Afzal; Din, Salahud (Ethnobotany Research and Applications, 2026)
Background: Local communities in Swat District, Pakistan, possess rich ethnobotanical knowledge of plant resources, developed through long-term interaction with their mountainous environment. This study aimed to document ethnobotanical practices, evaluate socio-cultural factors influencing knowledge retention and transmission, and identify plant species of high medicinal and cultural significance. Methods: Data were collected between 2018 and 2022 from 300 informants aged 20–90 years across seven Tehsils using structured and semi-structured interviews and group discussions. Quantitative indices including Use Value (UV), Relative Frequency of Citation (RFC), Fidelity Level (FL), and Informant Consensus Factor (ICF) were applied to assess plant significance. Statistical analyses such as chi-square tests, correlation analysis, and one-way ANOVA examined relationships between knowledge and socio-demographic variables. Results: The present study documented 234 plant species from 74 families. Dominant families were Poaceae (20%), Rosaceae (9%), Fabaceae (7%), Asteraceae (5%), and Brassicaceae (3%). Plants were mainly used for fodder (52%), medicine (42%), and fuelwood (25%). Leaves (42%) and fruits (19%) were the most utilized parts. Taxus wallichiana ranked highest (RFC = 0.60, UV = 0.90, FL = 100%), followed by Punica granatum and Ricinus communis. ICF values (0.92–0.98) indicated strong informant consensus. Knowledge varied significantly with gender, age, occupation, and ethnicity (p < 0.001), with a strong positive correlation between age and traditional knowledge (ρ = 0.60, p < 0.001). Conclusions: Indigenous knowledge remains vital for healthcare and livelihoods but faces threats from modernization. Community-based conservation is essential to protect biodiversity and ethnobotanical heritage. Keywords: Ethnobotany, Indigenous knowledge, Traditional medicine, Plant-use patterns, High-altitude flora, Swat Valley, Pakistan, Socio-cultural influences, Conservation strategies, Use Value, Relative Frequency of Citation, Medicinal plants, Sustainable utilization